2013
DOI: 10.1371/journal.pone.0065501
|View full text |Cite
|
Sign up to set email alerts
|

S100P Expression Is a Novel Prognostic Factor in Hepatocellular Carcinoma and Predicts Survival in Patients with High Tumor Stage or Early Recurrent Tumors

Abstract: The calcium-binding protein S100P is expressed in a variety of human cancer cells and is important in cancer cell growth and invasion. Using differential display, we found S100P is overexpressed in human hepatocellular carcinoma (HCC). We examined the expression of 305 unifocal, primary HCC tumors using immunohistochemistry. The S100P protein was expressed in 173 of the 305 (56.7%) HCC tumors. The expression of S100P correlated with female sex (P = 0.0162), high serum α-fetoprotein level (P = 0.0001), high tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…This squamocolumnar junction group included genes such as complement factor B and H ( Cfb , Cfh ), which are involved in the regulation of immune reaction and interferon-induced protein 44 ( Ifi44l ), which is also activated in anti-viral response. Interestingly, S100p gene, which is associated with Cell Cycle, Cell Growth and Invasion and reported to be a novel independent predictor for poor prognosis in colorectal and hepatocellular carcinoma [ 30 ], was also found upregulated only in vulvar cancer samples in our study. However, despite the high levels of its expression found also in cervical cancer patients, it was not considered differentially expressed ( p = 0.07), due to variation among the cancer samples.…”
Section: Resultssupporting
confidence: 56%
“…This squamocolumnar junction group included genes such as complement factor B and H ( Cfb , Cfh ), which are involved in the regulation of immune reaction and interferon-induced protein 44 ( Ifi44l ), which is also activated in anti-viral response. Interestingly, S100p gene, which is associated with Cell Cycle, Cell Growth and Invasion and reported to be a novel independent predictor for poor prognosis in colorectal and hepatocellular carcinoma [ 30 ], was also found upregulated only in vulvar cancer samples in our study. However, despite the high levels of its expression found also in cervical cancer patients, it was not considered differentially expressed ( p = 0.07), due to variation among the cancer samples.…”
Section: Resultssupporting
confidence: 56%
“…We have previously reported numerous ETR predictors, including various histopathological predictors (large tumor size, high tumor grade, and high tumor stage), a serum biomarker (high AFP levels), p53 mutation, and several molecular biomarkers such as stathmin and S100P. 14,17,34 In this study, we demonstrated for the first time that HNF1β-positive HCCs exhibit a higher risk of ETR than HNF1β-negative HCCs do. Shim et al also reported HNF1β expression as an independent prognostic factor after multivariate adjustment and that it can predict tumor recurrence and HCC-specific death after liver transplantation in patients with HCC.…”
Section: Discussionmentioning
confidence: 58%
“…Combined, these findings suggest that HNF1β expression can serve as a critical molecular predictor for the identification of patients with HCC who are at a higher risk of ETR after surgical resection or liver transplantation. Because ETR is a critical prognostic factor in HCC, 14,17,34 further stratification of patients based on these molecular factors might aid in achieving a more accurate prediction of patient survival and in developing superior patient management strategies. Therefore, further investigation of the possible prognostic factors in patients with HCC and ETR indicated that HNF1β expression exerted additional adverse effects on patient survival in patients with both ETR-positive and ETRnegative HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased S100P levels have been reported in liver, skin, endometrial, colon, and pancreatic cancers, and have been indirectly implicated in promoting carcinogenesis and cancer metastasis in animal models [ 5 , 6 , 16 - 18 ]. However, the exact molecular mechanism involved in the promotion of lung cancer cell progression remains unclear.…”
Section: Discussionmentioning
confidence: 99%